Optimisation study on the flavonoid extraction process from Abrus precatorius leaves and the comparison of total flavonoid content by HPLC and UV - Xujiang Yuan; Cuimin He; Xianmei Xue; Zhike Liang; Yanfen Chen (KeAi Communications Co., Ltd., 2023)
Abrus precatorius is a leguminous plant with high medicinal value. Its leaves are rich in flavonoids. There only are limited reports on the extraction process and quality assessment of total flavonoids in Abrus precatorius leaves (APL). This study presents the extraction process of total flavonoids in APL and its optimisation by response surface methodology (RSM). High-performance liquid chromatography (HPLC) and UV methods were used to determine the total flavonoid content and their differences were compared. The feasible extraction parameters of total flavonoids from APL were found to be 50% ethanol, a liquid-solid ratio of 50:1, an extraction time of 60 ​min and two extraction cycles. The number of extraction cycles was the main influencing factor. The total flavonoid content as determined by this optimised process was 69.0 ​mg/g by HPLC and 41.7 ​mg/g by UV. There was a significant difference between the total flavonoid content determined by the UV method and HPLC. A comparative analysis of 29 samples in RSM and 14 batches of APL showed that the total flavonoid content as determined by UV was only about half of that determined by HPLC. The factors that influence this difference and potential solutions to this challenge were discussed. The results of this study could lay a foundation for the quality assessment, standardisation, development and utilisation of flavonoids in APL.